Cognitive radio technology - Fette, Bruce Alan (Communications engineering series., 2006)
Cognitive radio technology is a smarter, faster, and more efficient way to transmit information to and from fixed, mobile, other wireless communication devices. Cognitive radio builds upon software-defined radio technology. A cognitive radio system is 'aware' of its operating environment and automatically adjusts itself to maintain desired communicationsits like having a trained operator inside the radio making constant adjustments for maximum performance. Operating frequency, power output, antenna orientation/beamwidth, modulation, and transmitter bandwidth are just a few of the operating parameters that can automatically be adjusted on the fly in a cognitive radio system. Fette has constructed a cutting-edge volume that hits all of the important issues including research, management, and support. Cognitive techniques will be discussed such as position and network awareness, infrastructure and physical and link layer concerns. Though still a nascent technology, cognitive radio is being pushed by the US military and for mission-critical civilian communications (such as emergency and public safety services). *The first book on a revolutionary technology that will be critical to military, emergency, and public safety communications *A multi-contributed volume written by the leaders in this exciting new area *Describes the location-determination capabilities of cognitive radio (the precise location of all units in a cognitive radio network can be determined in real time).